2013
DOI: 10.1002/adsc.201300591
|View full text |Cite
|
Sign up to set email alerts
|

Convenient and Reliable Routes Towards 2‐Aminothiazoles: Palladium‐Catalyzed versus Copper‐Catalyzed Aminations of Halothiazoles

Abstract: Two efficient methods for the amination of 2-halothiazoles are presented here. A first protocol requires a Pd/L system. Several 2-aminothiazoles were synthesized under optimized conditions and isolated in good yields. The first palladium-catalyzed C À N coupling reactions between 2-halothiazoles and primary alkylamines are presented. In a second part, ligand-free copper-catalyzed aminations of 2-halothiazoles by alkylamines and aniline in a green solvent have been developed. The protocol is very ef-fective for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 92 publications
0
13
0
Order By: Relevance
“…In contrast, in the second scenario, if the aryne approaches the carbon-lithium bond syn to the tBu group, the sulfinyl moiety would rotate 'counter-clockwise', forcing the tBu group to become pseudo-axial. application in the synthesis of monophosphine ligands for C-C and C-N coupling reactions, [17,20,46] diphosphines for asymmetric hydrogenation, [16,26] P-chirogenic derivatives, [15,18] phospholes [47] for hydroformylation as well as natural products like (-)-steganacin. [48,49] Actually, our group is now working on an enantioselective version.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the second scenario, if the aryne approaches the carbon-lithium bond syn to the tBu group, the sulfinyl moiety would rotate 'counter-clockwise', forcing the tBu group to become pseudo-axial. application in the synthesis of monophosphine ligands for C-C and C-N coupling reactions, [17,20,46] diphosphines for asymmetric hydrogenation, [16,26] P-chirogenic derivatives, [15,18] phospholes [47] for hydroformylation as well as natural products like (-)-steganacin. [48,49] Actually, our group is now working on an enantioselective version.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the C–N cross-coupling of 2-aminobenzothiazole (or its derivatives) with boronic acids, , aryl halides, triflates, or triazenes efficiently afforded the aminated products. Besides, treatment of amines with unsubstituted benzothiazole or 2-substituted benzothiazoles also enabled the efficient formation of the desired products (Scheme a). It was observed that all of the above reactions went through one amination sequence to furnish the mono-heteroarylation products.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the importance of 2‐ N ‐(alkylamino)azoles, a number of methods have been developed for their synthesis (Scheme ). The successful protocols for the synthesis of 2‐ N ‐(alkylamino)azoles involve aminations of halobenzothiazoles with alkylamines or cross‐coupling reactions between aminazoles and aryl halides, the direct oxidative couplings of azoles with amines or formamides, intramolecular cyclization of N ‐arylthioureas or ortho ‐halophenylthioureas, condensation of isothiocyanates with amines, Cu‐catalyzed condensation of sodium hydrosulfide with carbodiimide, Cu‐catalyzed/mediated three‐component condensation reactions, aerobic oxidative cyclization/dehydrogenation of thioureas and cyclohexanones and metal‐catalyzed N ‐alkylation of aminazoles with alcohols . Although the above procedures are generally practical and versatile, some of them still have various limitations such as the use of noble metals and additives, a longer reaction time, a limited substrate scope and the generation of many unwanted wastes.…”
Section: Introductionmentioning
confidence: 99%